THE INFLUENCE OF INFLATION, RETURN ON ASSETS (ROA), AND DEBT TO EQUITY RATIO (DER) ON STOCK PRICES OF FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FROM 2019 TO 2023 - Irfan Fernando Sijabat; Yogi Juventus Suratma Karokaro; Jessi Charina Sembiring; Dewi Simatupang (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study aims to analyze and test the influence of Inflation, Return On Assets (ROA), and Debt to Equity Ratio (DER) on the stock prices of Food and Beverage companies listed on the Indonesia Stock Exchange from 2019 to 2023. The independent variables in this research are Inflation, Return On Assets, and Debt to Equity Ratio. The dependent variable is the Stock Price. The population consists of 95 Food and Beverage companies listed on the Indonesia Stock Exchange during 2019 - 2023, and the sample includes 21 companies. Data testing and analysis were conducted using E Views 12 software with panel data. Using multiple linear regression analysis, the partial test results indicate that Inflation, ROA, and DER simultaneously do not affect stock prices. The partial test also shows that Inflation, ROA, and DER have no effect on the stock prices of Food and Beverage companies listed on the Indonesia Stock Exchange from 2019 to 2023, with a coefficient of determination of 5%.